Conserving moisture helps enhance almond yield - Kumar, Dinesh; Srivastava, K K; Singh, D B (Indian Horticulture, 2018)
Almond is a high-value crop in temperate region of India, particularly inKashmir valley. The moisture stress during summers is major constraint forgetting proper yield. To overcome this, an attempt was made to enhanceproductivity of rainfed almond orchards through different moistureconservation techniques where irrigation facilities are not available andsupplemental irrigation is also uneconomical. The full-moon, half-moon andtrench water harvesting techniques along with plastic mulch/grass mulchimproved the almond yield by conserving more moisture during nut growthand kernel-filling stage under rainfed condition.